Does Explicit Instruction Drive Improvement in Writing and Collocation? - Arlius, Yeni; Jufrizal (Universitas Hamzanwadi, 2024)
Explicit Instruction is an educational approach known for its structured and systematic method of teaching, which enhances various academic skills. While its impact on writing skills has been extensively explored, its potential benefits for young students in developing writing proficiency and collocation awareness have garnered interest. This study aims to determine the extent to which Explicit Instruction can improve students' awareness of collocations and writing skills among 25 young students of MTs Darussalam Amping Parak, West Sumatera, Indonesia. Data were collected from writing tasks, tests, observational checklists, and field notes as all participants underwent an Explicit Instruction intervention over two cycles. The findings show that during the first cycle, the average collocation test score was 53.64, with no students meeting the minimum achievement criteria, though this was an improvement from the pre-cycle average of 36.8. In the second cycle, the average score rose to 75.84, with 11 students surpassing the score of 75. For the writing test, the first cycle's average score was 69.96, with 9 students meeting the minimum standard, up from a pre-cycle average of 55.73. By the second cycle, the average writing test score increased to 82.37, with 20 students passing the minimum standard. These results indicate that Explicit Instruction can enhance students' awareness of collocations and improve their writing skills, suggesting that this instructional method is effective for young students and could be integrated into their writing curriculum to foster better writing proficiency.